(untitled) (Revista Contexto & Saúde, 2026)
The objective was to relate the practice of physical exercises with clinical conditions and functional capacity in elderly people living in the community. This is a cross-sectional study, with a population composed of elderly people registered in Health Units in the urban area of ​​Ijuí, Rio Grande do Sul. The inclusion criteria considered elderly people, both sexes, who agreed to participate in the study. Elderly people who were unable to respond and had caregivers hired for less than 30 days were excluded. Sociodemographic data, on the practice of physical exercises and health conditions were collected through structured interviews. Functional capacity was assessed by the Clinical-Functional Vulnerability Index-20. Data analysis was performed using the Statistical Program for Social Sciences software version 22.0, with nonparametric mean comparison test and Pearson’s chi-square test. It was found that the chance of an elderly person being hypertensive increased by 63%, while the chance of presenting multiple comorbidities increased by 83% in sedentary individuals compared to those who regularly practice physical exercise. Furthermore, sedentary elderly individuals demonstrated a 168% increased probability of presenting impaired functional capacity, 79% of having a history of falls, 274% of being unable to shop, 251% of being unable to manage finances, 126% of being unable to perform household tasks and 168% of being unable to bathe. It was also found that women, elderly individuals aged 80 or over and those without partners were more sedentary. It is concluded that the practice of physical exercise is related to clinical-functional condition.